When Ads Become Invisible: Minors’ Advertising Literacy While Using Mobile Phones - Beatriz Feijoo; Charo Sádaba (Media and Communication, 2022)
It has been traditionally estimated that children begin to understand the persuasive intent of advertising at about the age of 8 which is when they acquire the skills of adult consumers. The ability to identify and interpret the persuasive content that minors are exposed to via mobile phones was analyzed through semi-structured interviews of children aged 10 to 14 years along with their parents in 20 households. Although minors seem to be able to recognize the persuasive intent of advertising, this does not necessarily mean that they have a deep understanding of the new digital formats that combine persuasion and entertainment. Data analysis of the interviews shows low recognition of the persuasive intent of commercial messages that are not explicitly identified as such, particularly on social networks. Data collected after minors viewing of different examples allowed researchers to conclude that standardized advertising is mainly identified by its format. Three levels of advertising processing were detected in minors: the liking of the advertisement, the affinity for the advertised product, and the ability to contrast the claims with searches for comments, forums or opinions of influencers. Recent research verified that conceptual knowledge of the persuasive intention of the advertising does not suffice for minors to interpret the message, a fact that must be taken into account when developing advertising literacy. For parents, the amount of time spent on these devices and the type of use minors make of their cellphones or the relationships they establish on them are more relevant than exposure to advertising itself.